Нижнє місто Ольвії (основні етапи розвитку) - Лейпунська, Н.О. (Археологія, 2001)
У статті розглянуто основні етапи забудови та історії Нижнього міста від пізньої архаїки до римського часу. Встановлено соціальну топографію цієї частини міста. Исследование Нижнего города Ольвии, начатое в XIX в., продолжается до наших дней. К настоящему времени открыты культурные слои и строительные остатки, позволяющие составить картину застройки и исторической топографии этой части Ольвии. В конце архаическою времени здесь существовали гавань и отдельные земляночные структуры. Сохранность застройки V — начала IV в. до н. э. не даст возможности полно реконструировать планировку Нижнего города того периода. Ко времени эллинизма здесь сформировалась уличная, определилась социальная топография: в южной части жили наиболее богатые граждане полиса, в северной — средний слой свободного населения. Нижний город, особенно его северная часть, пережил пожар при осаде Зопириона и оползень в конце эллинизма. В римское время здесь находилось производственно-хозяйственное предместье. The investigation of the lower town of Olbia started in the 19th century and has been continuing to this day. To the present times, the cultural layers and building remnants that help to make up the picture of the building and historical topography of this part of Olbia have been discovered. At the end of the archaic time, there was a harbor and separate earthen structures here. The safety of the building of the V — the beginning of the IV centuries BC — doesn't permit the full reconstruction of the planning of the lower town of this period. During the Hellenistic time, street topography formed, and social topography was determined. The southern part was inhabited by the richest citizens of the polis, while the middle stratum of the free population inhabited the northern part. The lower town, especially its northern part, went through the fire during the siege of Zopirion and through the landslip at the end of the Hellenistic epoch. In Roman times, there was a production and economic suburb there.